TOTAL HEMOCYTE COUNT AND HEMOLYMPH GLUCOSE CONCENRATION RESPONSE OF SPINY LOBSTER Panulirus homarus ON RATIO OF SHELTER - Suhaiba Djai; Eddy Supriyono; Kukuh Nirmala; Kukuh Adiyana (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2017)
This research was conducted to assess the physiological response of the lobster Panulirus homarus for the ratio of the shelters. The method used completely randomized design with two replicates of each treatments with shelter ratio (A) 1 : 5, (B) 3 : 5, (C) 4 : 5, (D) 5 : 5. Weight average for 184 lobsters with the stocking density of 23 lobsters for each treatment was 32.64 ± 0.58 g. The experiment was conducted for 60 days. The lobster was fed with trash fish and acclimatized for 7 days before the experiment. Observations on the physiologycal of every 10 days. The physiological responses that observed were total hemocyte count (THC) and hemolymph glucose concentration. The results showed that 4:5 was the best lobster shelter ratio because it could reduce stress levels. This is indicated by the stable values of THC and hemolymph glucose level during the experiment and supported by the growth of 57.28 ± 0.15 g and survival rate of 91.31 ± 2.60%. Keywords: lobster, Panulirus homarus, ratio, shelter, THC, glucose